Detection and Analysis of Multi Signals Processing based on Curvelet Transform: a Survey Report - Subhani, Shaik (International Journal of Computer Sciences and Engineering, 2018)
Digital Signal Processing has a vast spectrum and does not end within electronics. It is the permissive technology for the origination, conversion, and understanding of data. The intention of this paper is to give a brief survey of curvelet transform for detection and analysis of signal processing. The curvelet transform is a family of mathematical appliances and overcomes the missing directional selectivity of wavelet transforms in images and signal analysis. The Curvelet handles curve discontinuities well; best spatial compare to wavelet transform to calculated stand for signals at dissimilar scales and angles. In order to improve the detection management, the conventional signal requires to be transformed into other field, in which the characteristic of the key signal is clearer. The paper is concluded with a brief discussion of curvelet transform implementations on digital signal processing.